Mechanical and durability properties of concrete using recycled granulated steel. (1st October 2016) - Quadir, Upal Mohammad Towfiqul; Islam, Kamrul; Billah, A.H.M. Muntasir; Alam, M. Shahria
Highlights: Performance of concrete containing RGS as a partial replacement of NFA is studied. The effect of RGS on the mechanical properties of concrete is investigated. Effect of sulphate exposure on RGS concrete is investigated. Microscopic analyses are conducted through SEM images. Optimum RGS content is found to be 30–50% by weight. Abstract: Recycled granulated steel (RGS) is a by-product produced in steel re-rolling mills which generate a significant volume of granulated steel each year. This paper describes the influence of RGS on the fresh, hardened, and durability properties of concrete, and compares these properties with those of control concrete specimens containing natural aggregates. RGS is introduced as a replacement of fine aggregates up to 60% by weight. All the tests are conducted in compliance with ASTM standards in compression and flexure under quasi-static loading condition. The results of the mechanical properties are presented in terms of compressive strength, splitting tensile strength, flexural strength and flexural toughness. The compressive and splitting tensile strength of various concrete mixes are determined after 28 and 56 days of curing where as flexural strength is determined after 28 days of curing. The study shows that both the fresh and hardened properties of RGS concrete are quite similar to those of the control concrete. However, with the increase of RGS the slump value increases compared to that of the control concrete. 28 days compressive strength, flexural strength, and flexural toughness increase up to 11%, 31%, and 38%, respectively, with the increase of RGS in the concrete mixtures compared to the control concrete. However, RGS concrete has a lower 28 days tensile strength compare to the control concrete. Furthermore, sulphate resistance of the RGS concrete is investigated extensively. Using scanning electron microscope (SEM) images, a comparison is performed with the unexposed specimens in terms of mechanical strength, physical impact (i.e., linear and volumetric shrinkage), and micro-structural transformation of concrete specimens. Finally, this paper addresses the possible use of RGS (a by-product) in concrete as a replacement of fine aggregate to produce sustainable concrete.